Editor's Note - Noonan, Ken (Journal of the Pediatric Orthopaedic Society of North America, 2021)
In this edition, we would like to highlight the amazing contributions from Wade Shrader and Grant Hogue over the last year. We are fortunate to have Wade’s Tutorial on Gait Analysis in Cerebral Palsy and Grant’s Symposium on Early Onset Scoliosis; both of these spanned the last year and are comprehensive reviews. I am sure you learned as much as I did from these excellent programs. When trying to accept change in our lives, it’s often been recounted, “the only constant is change.” Yet, Ben Franklin best expressed its value, “When you’re finished changing, you’re finished.” JPOSNA is now the official journal for POSNA, and we are changing from a singular educational journal to one that will begin publishing original research. While we are excited for this, we will continue to produce educational material that is highly valued. In this current edition, I would like to point out the obvious and the hidden. When reviewing the table of contents, hopefully you will recognize the contributions from colleagues from around the world—Singapore, Japan, and Australia. Perhaps this is best seen in Jennifer Laine’s triumphant collection of cases of congenital pseudarthroses of the tibia and with the opinions from surgeons from the USA, Korea, Norway, and India. JPOSNA seeks to be of value to pediatric orthopaedists worldwide; this edition moves in that direction. There are two important papers that may not seem relevant to some. Karen Bovid, Jaysson Brooks, and Michael Heffernan have written an essay on the Ethics of Outreach. It’s a MUST READ for anyone who does outreach, yet there is much we can all learn and adapt in our home practices. On the surface, the EOS paper by Hiroko Matsumoto and Brian Snyder may not appear to be of interest to the non-spine surgeon, yet it is a tutorial for anyone who wants to design and execute clinical research. JPOSNA seeks to be of value for all pediatric orthopaedists regardless of subspecialty interest. We believe these two papers highlight this focus. Exciting times for JPOSNA are here; our Society is refining its own Journal. As we grow, we welcome your comments, your questions, and any help you can provide to make our Journal the best it can be.